PULSE FORMATION OF STRUCTURE OF FOUNDRY ALUMINUM ALLOY - S. M. Usherenko; S. N. Grigoriev; E. I. Marukovich; Yu. S. Usherenko; A. A. Andrushevich (Литьë и металлургия)
The estimation of the impact of the SiC powder in the mode of super-deep penetration (SDP) and subsequent heat treatment on the evolution of the fine structure parameters of aluminum casting alloy Al-12%Si are made. Impulse impact on the alloy provided evolution of its structure at different scales. Thus a massive composite material reinforced with the fiber zones was obtained from aluminum alloy casting.